2018
DOI: 10.1159/000495713
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI)-Induced Autophagy Protects L-02 Hepatocytes from Apoptosis Through the ROS-AKT-mTOR Pathway

Abstract: Background/Aims: Hexavalent chromium [Cr(VI)] pollution has become a global concern for both ecosystems and human health. Our previous study revealed Cr(VI) could induce both apoptosis and autophagy in L-02 hepatocytes. Here, we sought to explore the underlying mechanism of Cr(VI)-induced autophagy and its exact role in cell death. Methods: Autophagy ultrastructure was observed under transmission electron microscope (TEM), autophagy flux was measured with double-tagged mCherry-green fluorescent protein (GFP)-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Several articles including our previous study, have demonstrated that Cr (VI) induced autophagy in cancer cells 23,25 . Autophagy acts as a cytoprotective mechanism in cells in order to maintain homeostasis primarily by degrading damaged organelles, malfolded proteins, and alien matter.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Several articles including our previous study, have demonstrated that Cr (VI) induced autophagy in cancer cells 23,25 . Autophagy acts as a cytoprotective mechanism in cells in order to maintain homeostasis primarily by degrading damaged organelles, malfolded proteins, and alien matter.…”
Section: Discussionmentioning
confidence: 88%
“…Several articles including our previous study, have demonstrated that Cr (VI) induced autophagy in cancer cells. 23,25 Autophagy acts as a cytoprotective mechanism in cells in order to maintain homeostasis primarily by degrading damaged organelles, malfolded proteins, and alien matter. Mitophagy is a selective form of macro-autophagy in which dysfunctional mitochondria are specifically targeted for autophagic degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study has suggested that Cr (VI)-induced oxidative stress can cause upregulated ROS, RNS, mitochondrial membrane damage, and elevated Bax: Bcl-2 ratio, and lead to apoptotic cell death (Navya et al, 2017). Some of the recent studies have confirmed that Cr (VI)-induced autophagy by activation of ROS-AKT-mTOR pathway mechanism (Liang et al, 2018). Apoptotic cell death is another important toxic mechanism of Cr (VI) toxicity, which lead to cell shrinkage, LDH leakage, mitochondrial membrane potential damage via activation of caspase cascades (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%